Analisis Pengendalian Kualitas Produk Songkok Menggunakan Metode Statistical Proses Control dan 5W+2H pada UD. Tiga Kunci - Rufaidah, Anik; Izzah, Nailul; Suparno, Suparno; Rosyidi, Moh Ririn (Universitas Teuku Umar, 2024)
In the period of the quality manufacturing sector, it is critical to pay attention to raw materials and product compatibility for consumers in order to preserve the quality supplied to them. Quality control is an important step in ensuring that the products produced fulfill defined specifications. Statistical Process Control (SPC) is a technique for monitoring and controlling the manufacturing process using statistical approaches. UD Tiga Kunci Songkok is a top manufacturer of high-quality songkok in Bungah Village, Gresik Regency, Indonesia. Established in 1985, our company has been dedicated to preserving the archipelago's traditions and culture by producing exquisite and comfortable songkok. Even yet, there are still flaws that arise at UD Songkok Tiga Kunci. Defects continue to develop throughout the last five months, from January to May 2024. There are 132 songkoks with faults. If this situation is not addressed, UD will suffer financial losses. Three Key Chompong aims to improve product quality and competitiveness by expanding the use of SPC in songkok production. Additionally, this 5W2H will address product defects. The research revealed that there are three sorts of faults that develop in UD Tiga Kunci: 45.5% of disorderly amounts, 40.2% of sloppy stitching, and 14.4% of velvet fabric, with the highest number of flaws. The control chart shows values of ucl=0.093, lcl=0, and cl/p ̅=0.043, indicating no deviation from the control line (despite the presence of flaws in the defect proportion). The factors that cause the most flaws in Songkok (untidy sum) are man, material, machine, and process. Knowing this, the corrective actions made at UD. Tiga Kunci keys monitor and evaluate each songkok manufacturing process to obtain mitigation procedures for songkok products.